Downsizing Bureaucracy: Impacts and Anticipation - Aditya Bagaswara; Lina Miftahul Jannah (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Administrative reform policies by governments are carried out to fix their bureaucracy. The aims is to create dynamic, agile, and professional bureaucracy through effectiveness and efficiency of organizational performance. Administrative reform is carried out by simplifying government organizations and improving bureaucratic procedures. However, downsizing bureaucracy has certain consequences/impacts. This article explains the concept of organizational downsizing as administrative reform, the impacts as a consequence of implementing the downsizing, and how anticipatory actions need to be prepared. The approach is carried out in a descriptive way, identifying problems, and solutions from the impacts of organizational downsizing. Identification is done by studying cases that have been carried out in various downsizing cases in the world. The impacts of implementing organizational downsizing based on research studies will generally occur in three domains, organizational matter, organizational human resources, and the external environment. Structural change may generate an internal conflict and the work issues. This problem if not well managed could affects organizational behavior, and organizational goals. Identification of significant impacts must be done before the implementation of downsizing. The role of leadership and management is important to prepare actions and instruments to anticipate negative impacts that may arise.